The importance microRNAs as a biomarker in lung cancer - Canatan, Duran; Sonmez, Yonca; Yılmaz, Ozlem; Coşkun, Hasan Şenol; Göksu, Sema Sezgin; Uçar, Selda; Aktekin, Mehmet Rıfkı (Acta Biomedica Atenei Parmensis, 2023)
Introduction: Lung cancer (LC) is the most common cancer in the world.Well known causes are long term smoking, environmental influences and genetic variations. LC is divided into two main types based on their histological phenotypes; small cell lung cancer (SCLC), and non-small cell lung cancer (NSCLC). The high specificity of these new screening methods, which are non-invasive, safe, inexpensive and simple to perform, is important in the early diagnosis and prognosis of cancer. MicroRNAs are significant biomarkers on the diagnosis metastasis and targeted therapies of NSCLC. In our study, we aimed to investigate the potential of using microRNAs as a biomarker in the early diagnosis of lung cancer. Material and method: Twenty patients diagnosed with lung cancer and twenty healthy individuals of the same age and gender were selected as the control group. Sixteen microRNAs were studied from blood samples. Result: Sixteen miRNAs (Let -7c, Let-7g, miR-1, miR-21, miR-29a, miR-31, miR-34a, miR 103a, miR-141, miR-155, miR-193b, miR-200b, miR-205, miR-340, miR-486, miR-708) were selected for tests and MiR 181 and miR 192 were used as the endogenous control group in line with their binding potentials and gene expression levels. The most specific and sensitive miRNAs were mirR-29a, miR-103a, and miR486 according to endogen controls in patients and healthy subjects. Discussion: A meta-analysis study showed that circulating miRNAs could be promising biomarkers for early diagnosis of lung cancer. Overall, 17 studies were included evaluating 35 miRNA markers and 19 miRNA panels in serum or plasma. The potential role of circulating miRNAs for non-invasive lung screening has been highlighted. In conclusion, there is a need for further validation studies for the use of three miRNAs as a biomarker in the early diagnosis and prognosis of lung cancer.